Strategi Pemasaran Coffeeshop Boy’s Selama Pandemi Covid-19 dengan Menggunakan Analisis SWOT - Adrinoviarini Adrinoviarini; Shinta Widyaningtyas; Ririn Fatma Nanda; Sofyan Hariyadi (Jurnal Social Economic of Agriculture, 2022)
Coffeeshop Boy's is one of the cafes that has survived the Large-Scale Social Restrictions (LSSR) and Enforcement of Restrictions on Community Activities (ERCA) policies during the pandemic. The power of investors and the quality of coffee are the reasons the Coffeeshop Boy's stay afloat. Coffee is a refreshing ingredient that comes from annual plantations. In Indonesia, farmers cultivate Robusta coffee and Arabica coffee, the difference between these two types of coffee can certainly be known from the taste. This research uses the descriptive qualitative method. Coffeeshop Boy's was originally a bottled coffee company that later turned into a home cafe. The LSSR and ERCA policies make this business must implement the right marketing strategy with the SWOT analysis method to find out the appropriate marketing strategy for this business in maintaining its business in the midst of a pandemic. The results of the SWOT analysis have shown that the total score of the IFAS matrix for strength items is 3.956 while for weakness items are 1.678. The results of the SWOT analysis have shown that the total score of the EFAS matrix for opportunity items is 3.241 while for threats items are 3.359. Based on the coordinates of the IFAS and EFAS matrices, Coffeeshop boy's is in quadrant 2 (ST Strategy) with a product diversification strategy. This has shown that Coffeeshop boy's can face the various threats that exist by taking advantage of the strengths they have. The ST strategy that needs to be implemented is to create new product innovations, provide special offers for new consumers, consumers who are having birthdays, or booking meetings, extend operational time, and create events to strengthen Coffeeshop Boy's branding.